Gain-of-function of the cytokinin response activator ARR1 increases heat shock tolerance in Arabidopsis thaliana - Sumudu Karunadasa; Jasmina Kurepa; Jan A Smalle (Plant Signaling & Behavior, 2022)
In addition to its well-established role in plant development, the hormone cytokinin regulates plant responses to biotic and abiotic stresses. It was previously shown that cytokinin signaling acts negatively upon drought and osmotic stress tolerance and that gain-of-function of the cytokinin response regulator ARR1 causes osmotic stress hypersensitivity. Here we show that increased ARR1 action increases tolerance to heat shock and that this is correlated with increased accumulation of the heat shock proteins Hsp17.6 and Hsp70. These results show that the heat shock tolerance of plants can be elevated by increasing the expression of a cytokinin response activator.